2019
DOI: 10.1177/0020764018815204
|View full text |Cite
|
Sign up to set email alerts
|

Implementing a community-based task-shifting psychosocial intervention for individuals with psychosis in Chile: Perspectives from users

Abstract: Background: Latin America, and Chile in particular, has a rich tradition of community mental health services and programs. However, in vivo community-based psychosocial interventions, especially those with a recovery-oriented approach, remain scarce in the region. Between 2014 and 20l5, a Critical Time Intervention-Task Shifting project (CTI-TS) was implemented in Santiago, Chile, as part of a larger pilot randomized control trial. CTI is a time-limited intervention delivered at a critical-time to users, is or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…One exception is a study we conducted in Santiago, Chile, which incorporated peer workers into a community mental health intervention, called Critical Time Intervention—Task Shifting (CTI-TS), to support users with schizophrenia ( 65 ). A qualitative study that evaluated the users' experience with CTI-TS found that the users felt a special connection and reciprocity with the peer workers, who had also experienced psychosis ( 66 ). One user commented that being with the peer worker was like “talking with someone who get and who gets you, with needing to talk or explain much,” whereas another said, “I felt reflect in the peer and tried to be like her, because she went through a situation like mine; she was always smiling, and didn't seem to be someone with problems, and so seeing her doing so well gave me strength.” We believe that adolescents who have had mental health problems, including suicidal conduct, and recovered can be a powerful source of support and orientation for their peers who are struggling with similar issues, and these connections can extend from innovative public health programs such as Project Clan to outpatient mental health centers, through the establishment of support groups, mentoring, and peer support services.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One exception is a study we conducted in Santiago, Chile, which incorporated peer workers into a community mental health intervention, called Critical Time Intervention—Task Shifting (CTI-TS), to support users with schizophrenia ( 65 ). A qualitative study that evaluated the users' experience with CTI-TS found that the users felt a special connection and reciprocity with the peer workers, who had also experienced psychosis ( 66 ). One user commented that being with the peer worker was like “talking with someone who get and who gets you, with needing to talk or explain much,” whereas another said, “I felt reflect in the peer and tried to be like her, because she went through a situation like mine; she was always smiling, and didn't seem to be someone with problems, and so seeing her doing so well gave me strength.” We believe that adolescents who have had mental health problems, including suicidal conduct, and recovered can be a powerful source of support and orientation for their peers who are struggling with similar issues, and these connections can extend from innovative public health programs such as Project Clan to outpatient mental health centers, through the establishment of support groups, mentoring, and peer support services.…”
Section: Discussionmentioning
confidence: 99%
“…One exception is a study we conducted in Santiago, Chile, which incorporated peer workers into a community mental health intervention, called Critical Time Intervention-Task Shifting (CTI-TS), to support users with schizophrenia (65). A qualitative study that evaluated the users' experience with CTI-TS found that the users felt a special connection and reciprocity with the peer workers, who had also experienced psychosis (66). One user commented that being with the peer worker was like "talking with someone who get and who gets you, with needing to talk or explain much, " whereas another said, "I felt reflect in the peer and tried to be like her, because she went through a situation like mine; she was always smiling, and didn't seem to be someone with problems, and so seeing her doing so well gave me strength."…”
Section: Limitations and Future Studiesmentioning
confidence: 99%
“…Similarly, in Rio, some users' stigma toward other mental health service users made them reluctant to go to CAPS for the intervention. Accordingly, implementation and dissemination of community-based EBIs for individuals with psychosis may benefit from including components that address the stigma surrounding severe mental illness (Agrest et al ., 2019 ). Our results are consistent with the broader mental health and stigma literature that interventions involving peers should also directly target internalized stigma among service users (Firmin et al ., 2017 ; Pyle et al ., 2018 ; Jones et al ., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Data were analyzed using the framework approach wherein the research team: (1) gained familiarity with the data by coding the first few transcripts; (2) inductively developed a thematic framework; (3) indexed codes according to the framework and resolved disagreements through consensus; (4) charted how themes and codes are connected to each other; and (5) mapping how the themes were similar or different across sites, and interpreted the results (Srivastava and Thomson, 2009 ). We developed a coding framework based on the core components of CTI-TS and prior analyses of the qualitative evaluation data (Agrest et al ., 2019 ). True to the framework method, open coding was also used, to allow for identification of additional themes.…”
Section: Methodsmentioning
confidence: 99%
“…Unfortunately, it is estimated that 66% of Nicaragua's municipalities have no access to mental health services (Sapag et al, 2013). In lieu of mental health professionals, there is evidence that suggests that community health workers such as the brigadistas can be taught to conduct health education programmes about mental health that will reduce stigma and educate people on to how to manage their problems (Agrest et al, 2019;Mutumba et al, 2013;Sibeko et al, 2018). In many areas of Nicaragua, brigadistas work closely with healthcare professionals to fill the gaps in health services and this is one to which they would be well suited.…”
Section: Discussionmentioning
confidence: 99%